Job Characteristics and Their Implications on the Satisfaction Levels of Call Center Employees: a study on a large telecommunications company - dos Anjos Grilo Pinto de Sá, Ana Cristina; Moura e Sá, Patricia Helena Ferreira Lopes de (Review of Business Management, 2014)
Standardization of answers and cost reduction efforts have provided a specific relevance to call centers in the commercial strategy of many service companies. The aim of this research is to analyze to what extent job characteristics, as identified by Hackman and Oldham (1980), are essential determinants for the level of satisfaction of the contact employee in a call center. Indeed, literature clearly suggests that job characteristics have a huge influence on employees´ work performance, their level of satisfaction, and, as a consequence, on the quality of services provided to the customers. In order to answer these questions, we have performed a case study, based on a questionnaire survey. Findings reveal that employees feel that their jobs are highly structured and that they are being closely monitored, what might worsen their performance regarding the contact with the customer, mainly in what concerns customization, flexibility and adequate answer in a single contact. In order to increase frontline employees’ performance, a proposal that enhances job autonomy and values intrinsic satisfaction is made. The research suggests the need to change the way companies view contact employee’s job, in a call center context, not always perceived and designed as strategic or determinant for customers’ satisfaction, which calls for additional institutional investment in the redesign of such job.